2007
DOI: 10.1111/j.1365-2133.2007.08168.x
|View full text |Cite
|
Sign up to set email alerts
|

Can automated dermoscopy image analysis instruments provide added benefit for the dermatologist? A study comparing the results of three systems

Abstract: Although the image analysis systems tested by us correctly identified the clinically obvious melanomas, they were not able to discriminate between most dysplastic naevi and early malignant melanoma. Thus, for the moment these computer-assisted diagnostic imaging machines provide little to no added benefit for the experienced dermatologist/dermoscopist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 20 publications
1
44
0
4
Order By: Relevance
“…CADx has been demonstrated to increase the diagnostic accuracy of trainees in the field of radiology. In dermatology, the benefits of the integration of CADx into the clinical diagnosis of pigmented skin lesions for dermatologists remain under investigation [26], [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…CADx has been demonstrated to increase the diagnostic accuracy of trainees in the field of radiology. In dermatology, the benefits of the integration of CADx into the clinical diagnosis of pigmented skin lesions for dermatologists remain under investigation [26], [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…37,38 A recent trial comparing three commercially available systems for diagnostic accuracy found that each one tended to overdiagnose suspect melanocytic lesions as melanoma and questioned whether they were ready to be used in clinical practice. 39 Nonetheless, logic dictates that with proficient training and programming, automated systems will eventually match, if not exceed, clinical diagnostic accuracy.…”
Section: Computer-assisted Diagnosis Of Pigmented Lesionsmentioning
confidence: 99%
“…Automated analysis of edges, colors, and shape of the lesion relies upon an accurate segmentation and is an important first step in any computer aided diagnosis system. Indeed, most commercially available systems show a great variability in reliability and specificity in the diagnostic process, and the image segmentation also varies greatly [3]. Irregular shape, nonuniform color, and ambiguous structures make the problem challenging [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of powerful and dedicated video cameras, the cost related to the acquisition material [25] or the actual usefulness of these instruments for dermatologists practising [3] may be the reasons that prevent their wide diffusion to physicians.…”
Section: Introductionmentioning
confidence: 99%